The Eddy Current Method of Alloy Drill Pipes Wall Thickness Evaluation: Impact Analysis; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Goldstein E. I. Ephrem Iosifovich (2019, 2019)
Title screen